Identifikasi Medication Error di Poli Interna Rumah Sakit X di Kota Manado - Citraningtyas, Gayatri; Angkoauwa, Leydia; Maalangen, Tiansi (Jurnal MIPA, 2020)
Medication error adalah suatu kejadian yang dapat merugikan bahkan membahayakan keselamatan pasien yang dilakukan oleh petugas kesehatan khususnya dalam hal pelayanan pengobatan pasien. Penelitian ini bertujuan untuk menentukan persentase medication error pada fase prescribing dan dispensing di Poli Interna Rumah Sakit X di Kota Manado. Penelitian ini merupakan penelitian yang bersifat analisis deskriptif dengan pengumpulan data secara prospektif. Hasil penelitian menunjukkan bahwa medication error yang terjadi pada fase prescribing antara lain tulisan resep tidak terbaca 3%, tidak ada nama dokter penulis resep 0,33%, tidak ada paraf dokter 0,33%, salah/nama pasien tidak jelas 4,98%, tidak ada usia pasien 72,75%, tidak ada konsentrasi/dosis sediaan 12,62%, tidak ada jumlah obat 0,33%, tidak ada bentuk sediaan 11,62%, dan tidak lengkap penulisan resep obat keras 0,66%. Sedangkan medication error pada fase dispensing meliputi pengambilan obat yang salah 0,33% dan jumlah obat yang diserahkan kurang 1,66%. Berdasarkan hasil penelitian maka dapat disimpulkan bahwa kejadian medication error di Poli Interna Rumah Sakit X di Kota Manado terbesar yaitu terjadi pada fase prescribing.Medication error is a condition that can harm and even endanger patient safety carried out by medical workers, especially in terms of patient treatment services. This study aims to determine the percentage of medication errors during the prescribing and dispensing phase at the Interna station of X Hospital in Manado City. This research is a descriptive analysis with prospective data collection. The results showed that medication errors that occurred during the prescribing phase included the recipe cannot be read 3%, no doctor's name in prescription 0.33%, no doctor's initial 0.33%, incorrect/unclear patient name 4.98%, no patient age 72.75%, no concentration/dosage of drugs 12.62%, no amount of drugs 0.33%, no dosage form 11.62%, and no complete prescription of prescription only medicine 0.66%. While medication errors in the dispensing phase include taking the wrong drug 0.33% and the amount of drug delivered is less than 1.66%. Based on the results of the study, it can be concluded that the incidence of medication errors at Interna station of X Hospital in Manado city mostly occurs in the prescribing phase.Medication error is a condition that can harm and even endanger patient safety carried out by medical workers, especially in terms of patient treatment services. This study aims to determine the percentage of medication errors during the prescribing and dispensing phase at the Interna station of X Hospital in Manado City. This research is a descriptive analysis with prospective data collection. The results showed that medication errors that occurred during the prescribing phase included the recipe cannot be read 3%, no doctor's name in prescription 0.33%, no doctor's initial 0.33%, incorrect/unclear patient name 4.98%, no patient age 72.75%, no concentration/dosage of drugs 12.62%, no amount of drugs 0.33%, no dosage form 11.62%, and no complete prescription of prescription only medicine 0.66%. While medication errors in the dispensing phase include taking the wrong drug 0.33% and the amount of drug delivered is less than 1.66%. Based on the results of the study, it can be concluded that the incidence of medication errors at Interna station of X Hospital in Manado city mostly occurs in the prescribing phase.